Forensic DNA Applications : an interdisciplinary perspective - Primorac, Dragan; Schanfield, Moses S. (Boca Raton : CRC Press, 2023)
"Forensic DNA Applications: An Interdisciplinary Perspective, Second Edition is fully updated to outline the latest advances in forensic DNA testing techniques and applications. It continues to fill the need for a reference book for people working in the field of forensic molecular biology testing and research as well as individuals investigating and adjudicating cases involving DNA evidence, whether they be civil or criminal cases. DNA techniques have greatly impacted obvious traditional forensic areas, but such advances have also positively affected myriad new areas of research and inquiry. It is possible today to think about solving forensic problems that were simply unheard of even a few years ago. As such, the book pulls all relevant research and applied science together into a detailed and comprehensive collection. Part I begins with the history and development of DNA typing and profiling for criminal and civil purposes. It discusses the statistical interpretation of results with case examples, mitochondrial DNA testing, Y single nucleotide polymorphisms (SNPs) and short tandem repeats (STRs), and X SNP and STR testing. It also explores low copy number DNA typing, mixtures, and quality assurance and control. Part II moves on to cover the various uses and applications of analyzing collected physical evidence, victim identification in mass disasters, analyzing animal DNA, forensic botany, and other unique applications. Part III is dedicated to the latest advances and developments in human molecular biology and Part IV looks at policies and laws and ethics governing DNA evidence, and its utilization in various cases and the courts. Forensic DNA Applications, Second Edition covers cutting-edge research and advancements in the field and is the most up-to-date reference available. Edited and contributed to by the world's foremost leaders in the field, it is a must-have reference for established professionals, and an essential resource to legal professionals-lawyers and judges dealing with civil and criminal cases involving DNA technology-as well as students entering the fields of genetics and forensic DNA analysis"- Provided by publisher.
Includes bibliographical references and index.
Keywords: Forensic genetics; DNA fingerprinting; DNA -- Analysis